Knowledge, Awareness And Practice Among General Dental Practitioners In Navi Mumbai Regarding Rehabilitation With Full Coverage Restoration In Children. - Nawal, Jha Mihir; Avanti, Ashwini; Sevekar, Shrirang; Shah, Devanshi; Saroj, Richa (Journal of Neonatal Surgery, 2025)
Background: Use of full coverage restoration in permanent teeth is well-known and highly used by dental practitioners as compared to primary teeth. Stainless steel crowns are an excellent option for restoring primary and young permanent teeth over conventional restorations. Methodology: A cross-sectional survey was done among 260 general dental practitioners in Navi Mumbai selected by a random convenience sampling method. A self-administered, multiple-choice questionnaire, validated by 4 independent experts, was used for the data collection. 16 multiple-choice questions concerning knowledge and practice of use of crowns, tooth preparation, how often primary crowns are placed by them in the clinic, most common treatment rendered in children, any difficulty faced by them and most difficult aspect of it. Result: 67.7% of the participants were females, while 32.3% were males. Out of the total participants, 79.2% treat children in their practice. 67.7% of the dentists did not have any additional qualification in pediatric dentistry. 42.9% treated 1–5 patients of the pediatric age group monthly, whereas 32.1% daily, and 25% weekly. 41.2% of them said they often call pediatric consultants. 89% of the participants commented that pulp therapy is the best treatment available for pulpally involved primary teeth, on the contrary 10.7% of them said extraction. The majority of dentists agreed to the necessity to restore pulpectomized teeth with a full coverage crown. Only 3.5% of dentists think that a stainless steel crown should not be given. Conclusion: There was considerable variation in the knowledge and practices of the general practitioners. The study concludes that there is a need to enhance their understanding of full-coverage restorations in pediatric dental rehabilitation..